Study of voluntary alteration of visual evoked potentials: Evaluating role in functional visual loss - Gupta, Sangeeta; Gupta, Gaurav; Singh, Surjit (International Journal of Research in Medical Sciences, 2017)
Background: Pattern reversal visual evoked potentials (PRVEP) are one of the recommended tests for detection of functional visual loss. However, voluntary alterations producing abnormal records have been reported in the normal subjects limiting the role of the test. Hence, this study aimed to record voluntarily altered PRVEP responses and to study the role of various modifications in the technique for detection of the condition. Methods: 20 normal subjects in the age-group of 18-25 years were studied. PRVEP records were obtained in the normal perceiving states and then with voluntary alterations in different stimulus conditions and the changes in the mean P100 latency and N75-P100 amplitude were compared and analysed using paired t-test. Results: 15 out of 20 subjects could voluntarily alter their PRVEP records with 26 out of 30 eyes demonstrating statistically significant abnormal records in terms of latency delay or amplitude reduction or both. Modifications in the technique with increased check size, field size and binocular stimulation reduced the number of abnormal records. But, mean P100 latency and N75-P100 amplitude recorded from the above stimulus conditions in voluntarily altered states were still statistically significantly altered from those in the normal perceiving conditions (p<0.05). Conclusion: Normal subjects can voluntarily produce abnormal PRVEP responses. Various modifications in the technique like increase in the check-size, field size and binocular stimulation should be employed if voluntary alteration is suspected, but interpretation should be made carefully in the context of clinical findings of the subject.